Current and future use of colchicine in patients with COVID-19 - Yu. Yu. Kiselev; A. V. Matveev; D. A. Sychev (Izdatelstvo OKI, 2020)
There exist some theoretical premises for the use of colchicine in patients with COVID-19, and clinical trials are underway. There is currently no published evidence confirming effectiveness and safety of colchicine in COVID-19 and allowing to recommend it for general practice. If prescribing colchicine, the one should perform clinical and hematological monitoring and avoid drug interactions.